Prevalence of epilepsy in Morocco: A population‐based study - Zouhayr Souirti; Mohammed Hmidani; Abdelaziz Lamkadddem; Kawtar Khabbach; Salma Belakhdar; Doae Charkani; Driss Mhandez Tlemcani; Nabila Lahmadi; Maroua El Akramine; Samira Erriouiche; Asmae Berrada; Asmae Ahniba; et al. (Epilepsia Open, 2023)
Abstract Objective In Morocco, there was a lack of data related to the epidemiology of epilepsy. This data serves as a useful basis for the development of any national intervention or action program against epilepsy in Morocco. Through this study, we aimed to estimate the active and lifetime prevalence of epilepsy in Morocco. Methods We collected data from eight out of 12 Moroccan regions in two steps: In the screening step, we first used a nationwide telephone diagnosis questionnaire and in the second stage, a team of physicians under the direction of an epileptologist conducted a confirmative survey for suspected cases. We fixed the confidence interval at α = 5% and the precision at 0.02. Results Up to 3184 responded positively to our invitation to participate in this study and were able to answer the questions of the first diagnostic questionnaire. In the diagnostic phase, physicians in neurology reinterviewed all 86 suspected cases using a confirmative diagnosis questionnaire, and 63 persons were confirmed as having lifetime epilepsy and 56 with active epilepsy. The mean age (Mean ± SD) of persons with epilepsy was 35.53 years (±21.36). The prevalence of lifetime and active epilepsy were 19.8 (19.6–20.0) and 17.6 (17.5–17.8) per 1000 (95% confidence interval), respectively. Significance This is the first study to estimate the active and lifetime prevalence of epilepsy in Morocco according to the international recommendations of the ILAE. The prevalence of lifetime and active epilepsy were 19.8 (15–24.6) and 17.6 (13.3–22.8) per 1000, respectively. We included both children and elderly subjects. The rates of active and lifetime population epilepsy prevalence in Morocco ranged between Asian and sub‐Saharan Africa low‐ and middle‐income countries.